Reviewing the Book “The Ethics of Science”:The Ethics of Science as a Branch of the Sociology of Science - Nawab Moqarrabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
As the title implies, The Ethics of Science: An Introduction, is a book on the science of ethics published by the Research Institute of Science and Religion of the Research Institute for Islamic Culture and Science in 2012. The English title is "The Ethics of Science: An Introduction", written by David B. Resnik and its translators are Mostafa Taghavi and Mahboubeh Morshedian. The ethics of science, which is a type of professional ethics in fact closely overlaps with various fields such as politics, society, ethics, religion, and economics. However, this field of ethics is more related to the sociology of science. In this article, the author first describes and explains the sociology of science, and then outlines a general design and an abstract of the contents of the book, and finally briefly reviews the deficiencies of the book.